2019
DOI: 10.1007/s42452-019-0706-y
|View full text |Cite
|
Sign up to set email alerts
|

Friction and wear behavior of karanja oil derived biolubricant base oil

Abstract: This work deals with the tribological performance of karanja oil trimethylolpropane ester (KOTMPE) biolubricant base oil for its probable application as automotive lubricant. The biolubricant was synthesized by transesterification of karanja oil methyl ester with trimethylolpropane (TMP) under acid catalyst. The study was made with Ducom TR30L four-ball tester at 1200 rev min −1 speed and 75 °C temperature over 60 min duration under normal loads of 15 kg and 40 kg as per ASTM D 4172-94 A and B standard test me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…It is observed that worn surfaces are rough with deep furrows distributed throughout the worn area. The base oil attaches its polar groups to the surface and non-polar groups form a protective layer between the rubbing surfaces (Sharma and Sachan, 2019). However, the protective layer formed by the base oil is unable to prevent the interaction between the steel balls and result in higher WSD with deep furrows.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that worn surfaces are rough with deep furrows distributed throughout the worn area. The base oil attaches its polar groups to the surface and non-polar groups form a protective layer between the rubbing surfaces (Sharma and Sachan, 2019). However, the protective layer formed by the base oil is unable to prevent the interaction between the steel balls and result in higher WSD with deep furrows.…”
Section: Resultsmentioning
confidence: 99%
“…Flash Temperature Parameter FTP ð Þ¼ w d 1:4 where w ¼ applied load (kg) and d ¼ mean WSD (mm). 26,27…”
Section: Flash Temperature Parametermentioning
confidence: 99%
“…Vegetable oils major consist of triglycerides, which are fatty-acid tri-esters of glycerol [7,8]. Vegetable oils are amphiphilic as a molecule contains both, polar and non-polar groups.…”
Section: Introductionmentioning
confidence: 99%